Social Media, Learning Media, and the Internet on Accounting Student's Interest in Learning During a Pandemic - Rahayu, Ruci Arizanda; Maryanti, Eny; Ni'mah, Siti Awalin (GREENOMIKA, 2023)
This study aims to determine social media, learning media and the internet on accounting students' interest in learning during a pandemic. This type of quantitative research with hypothesis testing. The data processed in this study consisted of students of the Muhammadiyah Sidoarjo University accounting study program class of 2018-2019. Observations made in this study by distributing online questionnaires to accounting students from the 2018-2019 class as a method of data collection. Then obtained as many as 220 respondents by using the slovin formula in sampling. The sampling technique used is probability sampling technique using simple random sampling. The analysis technique used in this study is the analysis technique of validity testing, reliability testing, and multiple linear regression analysis using SPSS Version 26 software. The results of this study prove that social media has a significant effect on accounting students' learning interest during a pandemic; learning media has a significant effect on accounting students' interest in learning during a pandemic; the internet has had a significant effect on the learning interest of accounting students during a pandemic.